Evaluating past and future contributions of conservation programs to species recovery - Rebeca E. Young; H. Resit Akçakaya; Elizabeth L. Bennett; Michael Hoffmann; Michael A. Hudson; Barney Long; Thalassa McMurdo Hamilton; Kelsey Neam; Megan A. Owen; Richard P. Young; Molly K. Grace (Conservation Biology, 2026)
Impact evaluation of conservation actions is a crucial step in global efforts to curb the biodiversity crisis. Through robust impact evaluation, practitioners can assess the effectiveness of conservation strategies and optimize the use of limited resources. Despite a proliferation of methods and tools for evaluating conservation impact, no standardized method exists to assess and compare the impact, and global contribution, of species recovery programs. To address this gap, we devised an evaluation framework, based on the International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), a global standard for measuring species recovery. We sought to provide a way for conservation program delivery partners to evaluate the effectiveness of their programs in contributing to global species recovery. We adapted 2 scenarios used in GSS assessments to estimate the impact of worldwide conservation actions on a species (the counterfactual current scenario and the future without conservation scenario), in order to propose a new assessment: the program GSS, a method allowing conservation practitioners to estimate the past and potential future impacts of a conservation program relative to the global impact. To identify the strengths and limitations of applying the GSS method at the program level and to gather proof of concept for our adaptation, we tested the proposed method on 16 species recovery programs. The program GSS approach identified past or future impacts of program actions on species status in 9 of the programs assessed. The detectability of program impact and the relative impact of the program compared with global impact were influenced by time since program establishment and program scope (i.e., proportion of a species’ population or distribution included in the program). Our framework for program GSS assessments can provide practitioners with a standard, straightforward, and cost‐effective way to communicate conservation successes and expected future impacts. Results from our program GSS framework can be compared with the global recovery of a species (conservation legacy and conservation impact) and thus indicate a program's contribution to the recovery of the entire species.